Assessing the impact of marine protected areas: a case study of the Perhentian Marine Park, Malaysia - Md. Nurul Islam, Gazi; Mohd Noh, Kusairi; Tai, Shzee Yew (2011)
Malaysia is rich in coral reef ecosystem. The country has 9,323 km of coastline and 3,600km2 of coral reef area. The coral reefs in the marine waters are the important habitats for fish species and destinations of tourists. This sector contributes benefits to the economy and livelihoods of many resource dependent households. The government has established Marine Parks to protect these coral reefs with a goal to conserve the habitats and to protect marine environment and valuable resources. However, fishing is not allowed in the marine protected areas (MPA) confined within two nautical miles from the shore. The marine habitats have been declined considerably over the years due to the use of destructive fishing gears, tourist activities and infrastructural development. The objective of this paper is to explore the importance of marine protected area through a community survey. The survey was conducted in Perhentian Island, east coast of Peninsular Malaysia to obtain opinions of the local people about the resource damage activities and preferences about community programmes. The results of this study are derived from a quota sample of 130 households who were interviewed with structured questionnaire and through informal discussions with various groups. The results showed that there were no major variations in the preference ranking among the various group of respondents. The findings of the study provide useful inputs for the policy makers for the planning and management of marine protected areas in Malaysia.